2009
DOI: 10.1007/s00259-009-1243-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive implications of bone turnover markers after palliative treatment with 186Re-HEDP in hormone-refractory prostate cancer patients with painful osseous metastases

Abstract: NTx, a potent collagenous marker of bone resorption, along with the novel NTx/PINP ratio provide useful cut-off values for identifying a group of patients suffering from painful osseous metastases from hormone-refractory prostatic carcinoma who do not respond to palliative treatment with (186)Re-HEDP. This information could help avoid an inefficient and expensive radionuclide treatment. Also, in the cohort of patients who will eventually undergo such treatment, the medium-term posttreatment changes in NTx offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In our study, 78.9% of patients experienced bone pain relief, and a therapeutic efficiency of 50%-92% has been reported with low-dose 186 Re-HEDP in different malignancies (13,14). This variation could be related to some heterogeneous factors such as patient selection criteria, tumor type, response criteria, and the method of administration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our study, 78.9% of patients experienced bone pain relief, and a therapeutic efficiency of 50%-92% has been reported with low-dose 186 Re-HEDP in different malignancies (13,14). This variation could be related to some heterogeneous factors such as patient selection criteria, tumor type, response criteria, and the method of administration.…”
Section: Discussionmentioning
confidence: 88%
“…Patient showed complete response to therapy and flare reaction after receiving 2,960 MBq of 186 Re-HEDP. bone markers, hemoglobin level, and previous treatments (14,23,24,36), but highly controversial issues remain. Although several studies have demonstrated that earlier treatment in patients in better clinical condition may improve the response rate (22)(23)(24), unfortunately radionuclide therapy is underutilized in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zafeirakis A et al [11] evaluated patients with hormone refractory prostate cancer and BM. They concluded that in this context NTx was useful when it comes to distinguishing the patients with bone pain who respond to the palliative treatment with biphosphonates from those who do not.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also have begun to explore correlations between bone marker level changes and response to palliative radionuclide treatment [35]. In a pilot study in men with painful osseous metastases from prostate cancer receiving palliative Re-186 treatment, a post-treatment NTX level decrease of at least 20% correlated with 3.4-fold belter palliation of bone pain (vs. men with <20% reduction in NTX levels; P = 0.0005) [35].…”
Section: Potential Insights From Bone Marker Assessments Throughoumentioning
confidence: 99%
“…In a pilot study in men with painful osseous metastases from prostate cancer receiving palliative Re-186 treatment, a post-treatment NTX level decrease of at least 20% correlated with 3.4-fold belter palliation of bone pain (vs. men with <20% reduction in NTX levels; P = 0.0005) [35]. Although this study involved a small number of patients, the findings are important because none of the patients received any other therapies that could affect bone metabolism [35]. …”
Section: Potential Insights From Bone Marker Assessments Throughoumentioning
confidence: 99%